METODOLOGI PENGHAKIMAN DAN PENULISAN TEKS ALASAN PENGHAKIMAN HAKIM SYARIE MELALUI PENDEKATAN ARAHAN AMALAN MAHKAMAH SYARIAH DI MALAYSIA : The Methodology of Judgment and Grounds of Judgment`s Text Writing by Syariah Judges According to Syariah Court Practice Directions Approach in Malaysia - Mahmod, Zulzaidi; Buang, Ahmad Hidayat (Jurnal Syariah, 2023)
The judgment and the grounds of judgment’s text writing by Syariah Judges are important aspects of justice in the Syariah Courts’ proceedings. The purpose of this research paper is to observe the methodology of judgment and grounds of judgment’s text writing by Syariah Judges according to Syariah Court’s Practice Directions. The research method applied in this paper is based on qualitative approach. This study has revealed that there are some approaches in Syariah Court’s Practice Directions that need to be referred by the Syariah Judges in preparing judgments and in the grounds of judgment’s text writing. Department of Syariah Judiciary Malaysia has taken the initiative to explain and conduct training about the application of Syariah Court’s Practice Directions participated by all Syariah Officers including Syariah Judges throughout Malaysia. Therefore, the Syariah Judges can comply with the implementation of this matter accordingly. Educating the Syariah Judges about such a matter constantly may improve the skills and enhance the competency of Syariah Judges.